Application of the Multidimensional Fatigue Inventory to Ethiopian Cancer Patients - Wondie, Yemataw; Hinz, Andreas (Frontiers in Psychology, 2021)
Objectives: Fatigue is a frequent debilitating symptom associated with cancer. However, scientific data on cancer-related fatigue is scarce in developing nations. This work examines psychometric properties of the multidimensional fatigue inventory (MFI-20) and analyzes the level of fatigue among Ethiopian patients with cancer in comparison with data from Germany. Methods: A sample of 256 patients with cancer drawn from a hospital in Ethiopia was examined with the MFI-20 and the European Organization for Research and Treatment of Cancer Quality of Life questionnaire (EORTC QLQ-C30). A comparative sample of 780 German patients with cancer served as the control. Results: The MFI-20 scales and total score showed acceptable reliability (α = 0.60–0.93) with a considerable convergent validity between MFI-20 and the EORTC QLQ-C30 fatigue scale (r = 0.67–0.75). The Ethiopian patients with cancer reported higher levels of fatigue than the German patients. Analyses of variance showed that Ethiopian patients with cancer who were illiterate, having advanced cancer, and those who did not receive either surgery or chemotherapy reported especially high levels of fatigue. Conclusion: The MFI-20 is a fairly reliable and valid instrument to be used with Amharic speaking patients with cancer. The high level of fatigue in these patients implies that appropriate cancer care is needed in developing countries.